Efektivitas Penggunaan Media Augmented Reality berbasis Pendekatan Joyful Learning Terhadap Kognitif dan Literasi Digital Siswa - Meilinda, Dhuwi Putri; Prasetyo, Dodi Rahayu (PENDIPA Journal of Science Education, 2025)
The purpose of the study was to determine the effectiveness of the use of Augmented Reality (AR) media based on the Joyful Learning approach to cognitive abilities and digital literacy of students and describe students’ perceptions of learning on the material of the circulatory system. This study used a quantitative approach with a pre-experiment One Group Pretest-Posttest Design. The research subjects were 35 students from Class VIII of SMP Negeri 1 Gebog. The data collection process was through multiple choice tests (pretest and posttest) and digital literacy scores. Wilcoxon test results showed a significance of 0.000 (<0.05), indicating a difference. The average value of N-Gain is 0.5790, indicating the effectiveness of learning. The digital literacy questionnaire shows an average score of 41.83 (83.66%) which is in the high-very high category. The results of the study state that Augmented Reality (AR) media combined with the Joyful Learning approach is said to be effective in improving learning outcomes (cognitive), digital literacy and positive student perceptions of science learning.